Improving racing drones flight analysis: a data-driven approach using motion capture systems - Castiblanco Quintero, Jose M.; Garcia-Nieto, Sergio; Simarro, Raul; Ignatyev, Dmitry (MDPI, 2024)
The publication of the previous study, titled “Experimental Study on the Dynamic Behaviour of Drones Designed for Racing Competitions”, highlighted the increasing interest in employing scientific methods for their design and analysis. That study examined the flight data of 15 racing drones within a large flight area, using Doppler-type sensors for data collection. Building on these findings and seeking to enhance them, the current work introduces an upgraded data acquisition system utilising optical sensors, thereby improving measurement accuracy. These enhanced flight data facilitate the development of updated quality indices and conclusions, offering a more precise and definitive analysis than was previously possible.
Keywords: 4605 Data Management and Data Science; 46 Information and Computing Sciences; 40 Engineering; drone; airframe; high performance; structure design; data analysis; agile; flight dynamics